Numerical Evaluation of Algebraic Cryptography - Gudapati , Ravindra Babu; Jha, Rajeev (International Journal of Membrane Science and Technology, 2023)
Introduction: A secret sharing scheme is a mechanism to divide up shares of a secret among numerous participants such that authorised groups of participants may piece it together but banned groups remain in the dark. Aim of the study: the main aim of the study is Algebraic Cryptography: Its Significance and Issues. Material and method: In this study, only black and white covert pictures are discussed. Although there exist visual cryptographic paradigms that deal with colour pictures and grayscale images, such circumstances are not considered in this study. Conclusion: We have proposed a construction and analysis of a t-(k, n) -VCS for monochrome pictures, where t participants are crucial in a (k, n)-VCS, based on a linear algebraic method.